Mitochondrial redox modulation of NLRP3 inflammasome in differentiated THP-1 cells - Abas, Razif; Wozniak, Marcin; Herbert, Karl (Universiti Putra Malaysia, 2019)
Introduction: Innate host defence against pathogen required NLRP3 inflammasome activation. Two steps of inflammasome complex activation are identified: Signal 1 or priming (expression of NLRP3 protein, pro-IL-1β, pro-IL-18 and pro-caspase-1), followed by Signal 2 or activation (expression of active IL-1β and IL-18). The purpose of this study was to investigate the possible mitochondrial role of superoxide generators and slow-release hydrogen sulfide generation in activating the NLRP3 inflammasome in THP-1 and endothelial cells (HUVEC and EA.hy926 cells). Methods: THP-1 cells were differentiated with PMA (5 ng/ml) up to 3 days. Later, LPS treatment (5 µg/ml) was administered for 24 h for Signal 1 priming followed by bzATP (300 µM) for 1 hour for Signal 2. Subsequently, the effects of intracellular generation of superoxide (mitoparaquat and paraquat at 1 and 5 µM) and hydrogen sulfide (GYY4137 and AP39) were investigated in differentiated THP-1 cells before and after LPS. Results: NLRP3 inflammasome activation were up-regulated in differentiated THP-1 cells. However, only EA.hy926 showed Signal 2 activation. The higher concentration of mitoparaquat (5 µM) was able to increase Signal 2. Interestingly, both slow-release hydrogen sulfide donors were able to reduce Signal 2 NLRP3 inflammasome. However, no active caspase-1 expression was observed. Conclusion: The effects of pro- and anti- inflammatory properties were observed by modulating IL-1β and IL-18 synthesis in differentiated THP-1 cells via redox active oxygen and sulfur species. Hence, promoting anti-atherosclerotic properties.